Blink and you die - Child, Lauren (Child, Lauren. Ruby Redfort (Series), 2019)
Thirteen-year-old genius and undercover agent Ruby Redfort finds herself dealing with a terrifying series of threats that suggest that one of the people closest to her has betrayed her.